PENGARUH METODE MEMBACA TERBIMBING TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS III SD YPK ALFA OMEGA WAISAI - Arthur Teny Remiasa; Desti Rahayu; Roni Andri Pramita (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
One of the goals of beginning reading is so that students can read simple words and sentences fluently and precisely. The aim of this research is: to determine the effect of the guided reading method on the beginning reading abilities of third grade students at SD YPK Alfa Omega Waisai. In this research, researchers used quantitative research. The research that will be carried out in this research is experimental research, the type of research is Quasi Experimental type Nonequivalent Control Group Design. The design used in this research is "Pretest-Posttest Control Group Design".This research was carried ou ton13 June–20 June 2024.The location of this research was SD YPK ALFA OMEGA Waisai. The sample in this study was thir dgrade, totaling 23 students as the control class third grade A and third grade B, totaling 25 students, as the experimental class. The reason was because in third grade A and third grade B, observations were made and it was found that students' initial reading abilities were not optimal. Test this hypothes is using thet-test. Thet-test is used to determine whether or not there is a significan tdifference between the post-test results of the experimental group and the control group.Based on the analysis results,it was obtained that ????????????????????????=2.067while ????ℎ????????????????????=13.428.So that ????ℎ????????????????????> ???????????????????????? and the significance value is 0.00<0.05.Thus,the influence of the guided reading method on the beginning reading abilities of third grade III students at SD YPK Alfa Omega Waisai.